DOES HEDONIC AND UTILITARIAN MOTIVES AFFECTS INTENTION TO FOLLOW GREEN ACCOUNT? OPINION LEADERSHIP AS A MEDIATING - Sakhina, Adinda Mutiara Putri; Kuswati, Rini (Jurnal Bisnis dan Manajemen (JBM), 2024)
Many business people use social media as a marketing tool in this digital age. TikTok is one of the social media platforms that is frequently utilized as a tool for product marketing. The number of followers on a TikTok account dramatically impacts how well a product is marketed through TikTok social media. This study tries to analyze the mediation effect of opinion leadership on the relationship between hedonic motives and utilitarian motives on intention to follow green account. This study used a sample size of 200 respondents who knew account TikTok of The Body Shop Indonesia. The sampling method used non-probability sampling with a purposive sampling approach. Data analysis using the SmartPLS application. The research findings show that hedonic and utilitarian motives directly affect opinion leadership, hedonic and utilitarian motives directly affect intention to follow the green account, and opinion leadership affects intention to follow the green account. The mediation effect test shows that opinion leadership is proven to mediate the influence of hedonic and utilitarian motives on the intention to follow the green account. Keywords: Hedonic Motives, Utilitarian Motives, Opinion Leadership, and Intention to Follow Green Account Abstrak Banyak pebisnis yang menggunakan media sosial sebagai alat pemasaran di era digital ini. TikTok merupakan salah satu platform media sosial yang sering digunakan sebagai alat pemasaran produk. Jumlah followers sebuah akun TikTok memiliki pengaruh yang besar terhadap seberapa baik sebuah produk dipasarkan melalui media sosial TikTok. Penelitian ini mencoba untuk menganalisis pengaruh mediasi opinion leadership terhadap hubungan antara hedomic motives dan utilitarian motives pada intention to follow green account. Penelitian ini menggunakan jumlah sampel sebanyak 200 responden yang mengetahui akun TikTok The Body Shop Indonesia. Metode pengambilan sampel menggunakan non probability sampling dengan pendekatan purposive sampling. Analisis data menggunakan aplikasi SmartPLS. Temuan penelitian menunjukkan bahwa hedonic dan utilitarian motives secara langsung berpengaruh terhadap opinion leadership, hedonic dan utilitarian motives secara langsung berpengaruh terhadap intention to follow green account, dan opinion leadership berpengaruh terhadap intention to follow green account. Uji efek mediasi menunjukkan bahwa opinion leadership terbukti memediasi pengaruh hedonic motives dan utilitarian motives terhadap intention to follow green account. Kata Kunci : Hedonic Motives, Utilitarian Motives, Opinion Leadership, dan Intention to Follow Green Account